2018
DOI: 10.1080/13621718.2017.1399574
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and fatigue properties of friction stir welded high-strength steel plates

Abstract: The weldability of high-strength steels (HSSs) is limited by their loss of strength, toughness and fatigue properties. In demanding applications, the fatigue properties of welds are among the strictest requirements. This paper presents a weldability analysis focusing on the microstructure and fatigue properties of 6 mm thick S690 and S355 HSS plates joined by friction stir welding. Their fatigue properties are compared to design recommendations and to fatigue properties obtained with other welding techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
2
7
0
3
Order By: Relevance
“…Microstructural stability is more in acicular ferrite compared to bainite in higher temperatures. 1,40 The obtained ferrite structures in the SZ microstructures are consistent with the results reported in the literature. 41,42 The low cooling rate welds (~8.33–5.55°C/s) developed polygonal ( α p ) and allotriomorphic ferrite as the major constituents in the stir zone microstructure as depicted in Figure 6(b) to (d).…”
Section: Resultssupporting
confidence: 90%
“…Microstructural stability is more in acicular ferrite compared to bainite in higher temperatures. 1,40 The obtained ferrite structures in the SZ microstructures are consistent with the results reported in the literature. 41,42 The low cooling rate welds (~8.33–5.55°C/s) developed polygonal ( α p ) and allotriomorphic ferrite as the major constituents in the stir zone microstructure as depicted in Figure 6(b) to (d).…”
Section: Resultssupporting
confidence: 90%
“…In comparison with the application of a single pass advanced welding solutions to modern TMCP HSS with a minimum yield strength of 700 MPa, as demonstrated by Sorger et al [14,15] in the application of friction stir welding with faster welding speed conditions, or Górka et al [16] in the application of hybrid laser arc welding, the multi-pass fusion welding can induce excessive decrease of impact-toughness, eventually due to the intercritically reheated domains that are formed in the HAZ [17,18]. On this scope, Hu et al [19] observed that V-N micro-alloying improved the toughness of the ICCGHAZ (inter-critically reheated coarse grained heat affected zone) by decreasing the size of M/A (martensitic/austenitic) constituents and refining the ferrite forming on the prior austenite grain boundaries [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sorger, ym. [11] vertasivat kitka-ja MAG-hitsattujen päittäisliitosten väsymiskestävyyttä S355-ja S690 -teräksillä. MAG-hitsattujen S690-teräksen päittäisliitoksille saatiin väsymisluokaksi (97,7 %) 234 MPa kaltevuuskertoimella m = 4,1, kun lämmöntuonnin mukainen jäähtymisaika t8/5 oli 5 s ja väsytyskokeissa käytettiin jännityssuhdetta R = 0,1.…”
Section: Väsymiskestävyysunclassified
“…Kirjallisuudessa on raportoitu väsytyskokeita ultralujien teräksien hitsausliitoksille ja näiden perusteella on myös kehitetty tarkempia väsymislaskentamenetelmiä [10][11][12]25]. Väsytystestauksesta poiketen tässä tutkimuksessa tarkastellaan hitsatun liitoksen poikkileikkauksia (Kuva 1.…”
Section: Loven Vaikutukset Hitsausliitoksessaunclassified
See 1 more Smart Citation